Pharmacological inhibition of complement C5a‐C5a(1) receptor signalling ameliorates disease pathology in the hSOD1(G93A) mouse model of amyotrophic lateral sclerosis - Lee, John D (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: Amyotrophic lateral sclerosis (ALS) is a fatal and rapidly progressing motor neuron disease without effective treatment. The complement system is up‐regulated in ALS, with recent studies indicating that the activation product C5a accelerates disease progression via the C5a(1) receptor (C5aR1). We therefore examined the therapeutic effect of C5a(1) receptor antagonism in hSOD1(G93A) mice, the most widely used preclinical model of ALS. EXPERIMENTAL APPROACH: The selective and orally active C5a(1) receptor antagonist, PMX205, was administered to hSOD1(G93A) mice in drinking water, both pre‐ and post‐disease onset. Blood, brain and spinal cord pharmacokinetics were performed using LC–MS/MS methods. Effects of PMX205 on hSOD1(G93A) disease progression was determined using body weight, hindlimb grip strength, survival time and blood analysis. KEY RESULTS: PMX205 entered the intact CNS at pharmacologically active concentrations, with increased entry observed in hSOD1(G93A) mice as the disease progressed, in line with augmented blood–brain barrier breakdown. hSOD1(G93A) mice treated with PMX205 before disease onset had significantly improved hindlimb grip strength, slower disease progression and extended survival, compared with vehicle treatment. These improvements were associated with reductions in pro‐inflammatory monocytes and granulocytes and increases in T‐helper lymphocytes in peripheral blood. PMX205 treatment beginning 3 weeks following disease onset also attenuated disease progression, significantly extending survival. CONCLUSION AND IMPLICATIONS: These results confirm that C5a(1) receptors play a pathogenic role in hSOD1(G93A) mice, further validating the C5a‐C5a(1) receptor signalling axis as a potential therapeutic target to slow disease progression in ALS.